Introduction to String Field Theory (Advanced Series in Mathematical Physics - Siegel Warren (World Scientific, 1989)
For anyone interested in the rapidly developing field of string theory (graduate students with the proper physics background), Siegel's book is a particularly good introduction. " B R Parker Choice, USA, 1989 "Siegel has played a major role in the application of BRST formalisms for quantization to string theory ... Siegel's book is of great interest for those who intend to do research in string field theory." O W Greenberg Foundations of Physics, USA, 1991